Explaining changes in higher education administrative work, influence, and authority: an examination of assessment administration in English higher education - Verney, Charlotte (2022)
This thesis explores changes in the authority and influence of English higher education administrators over university work. To conduct this exploration, I drew on Andrew Abbott’s system of professions, to explain how and why higher education administrators have become more involved in assessment, a core academic area of higher education learning and teaching.